Engineered nanomaterial based implantable MicroNanoelectrode for in vivo Analysis: Technological advancement and commercial aspects - Divya; Ghosh Dastidar M.; Mahapatra S.; Kumari R.; Dkhar D.S.; Roy S.; Chandra P. (My University, 2025)
In vivo monitoring of essential biomolecules is crucial to address numerous critical diseases such as diabetes, cancer, and different neurological disorders that require continuous, rapid, and trace level recognition. In recent years, implantable biosensors conjugated with different kinds of nanomaterials are being used for in vivo detection as it supports minimal tissue invasion. Considering nanomaterials to design advanced in vivo biosensors has shown a substantial effect on imaging, diagnostics, and therapeutics. Nanomaterials i.e., nanoparticles, carbon fibers, dendrimers, quantum dots and nano-conjugates, have offered better biocompatibility, sensitivity, selectivity, and low detection limit to these in vivo opto-electrochemical biosensing platforms. In this article, the deployment of different kinds of nanomaterial for the fabrication of various in vivo sensors have been elaborated and discussed with various examples. Types of nanomaterial, analytes, mechanism, microelectrode dimensions, transduction system, testing model, and analytical details of such in vivo nano/micro sensors have been tabulated in detail. This article aims to provide a broader perspective regarding in vivo micronano sensors as in recent times, more interest has grown towards specified and real time detection in clinical settings. Various commercially available devices for in vivo monitoring have also been discussed. Major challenges during experimentation and their possible confronting strategies have also been depicted vividly. © 2023